Auditory Dysfunction in Patients with Cerebrovascular Disease - Sadaharu Tabuchi (The Scientific World Journal)
Auditory dysfunction is a common clinical symptom that can induce profound effects on the quality of life of those affected. Cerebrovascular disease (CVD) is the most prevalent neurological disorder today, but it has generally been considered a rare cause of auditory dysfunction. However, a substantial proportion of patients with stroke might have auditory dysfunction that has been underestimated due to difficulties with evaluation. The present study reviews relationships between auditory dysfunction and types of CVD including cerebral infarction, intracerebral hemorrhage, subarachnoid hemorrhage, cerebrovascular malformation, moyamoya disease, and superficial siderosis. Recent advances in the etiology, anatomy, and strategies to diagnose and treat these conditions are described. The numbers of patients with CVD accompanied by auditory dysfunction will increase as the population ages. Cerebrovascular diseases often include the auditory system, resulting in various types of auditory dysfunctions, such as unilateral or bilateral deafness, cortical deafness, pure word deafness, auditory agnosia, and auditory hallucinations, some of which are subtle and can only be detected by precise psychoacoustic and electrophysiological testing. The contribution of CVD to auditory dysfunction needs to be understood because CVD can be fatal if overlooked.